Influencia del perfil del Docente en el desarrollo de la identidad y convivencia en los niños de 3 años del Jardín Nº 215-de la ciudad de Trujillo del año 2015 - Cabanillas Yika, Kristel Rocío de María (2017)
This work was aimed at determining the influence of the teacher profile in the development of identity and coexistence of children under 3 years. _x000D_ The professional profile is part of a perspective of human resource management in core skills; therefore, promotes the formation of a trained and authorized especially for effective performance in their practice teaching professional. _x000D_ The development of identity and coexistence implies that the student build social relationships from the condition that we as subjects of law and from fulfilling our duties as citizens. In that sense, it involves establishing relationships of respect, solidarity and equity that promote intercultural dialogue. _x000D_ This research was conducted descriptive; its purpose was applied; depth was descriptive level. _x000D_ The sample population of this study consisted of all children 3 years old enrolled in the Kindergarten Nº. 215, of which there are 91 children, distributed in the Jasmine classrooms, Rainbow and Celeste with 31, 31 and 33 children respectively. _x000D_ The instruments were applied between July and October 2015, in the Kindergarten N°. 215.